Desmoplastic small round cell tumor: from state of the art to future clinical prospects. Issue 5 (4th May 2023) - Hovsepyan, Shushan; Giani, Claudia; Pasquali, Sandro; Di Giannatale, Angela; Chiaravalli, Stefano; Colombo, Chiara; Orbach, Daniel; Bergamaschi, Luca; Vennarini, Sabina; Gatz, Susanne Andrea; Gasparini, Patrizia; Berlanga, Pablo; et al.
ABSTRACT: Introduction: Desmoplastic small round cell tumor (DSRCT) is an extremely rare and highly aggressive soft tissue sarcoma, presenting mainly in male adolescents and young adults with multiple nodules disseminated within the abdominopelvic cavity. Despite a multimodal approach including aggressive cytoreductive surgery, intensive multi-agent chemotherapy, and postoperative whole abdominopelvic radiotherapy, the prognosis for DSRCT remains dismal. Median progression-free survival ranges between 4 and 21 months, and overall survival between 17 and 60 months, with the 5-year overall survival rate in the range of 10–20%. Area covered: This review discusses the treatment strategies used for DSRCT over the years, the state of the art of current treatments, and future clinical prospects. Expert opinion: The unsatisfactory outcomes for patients with DSRCT warrant investigations into innovative treatment combinations. An international multidisciplinary and multi-stakeholder collaboration, involving both pediatric and adult sarcoma communities, is needed to propel preclinical model generation and drug development, and innovative clinical trial designs to enable the timely testing of treatments involving novel agents guided by biology to boost the chances of survival for patients with this devastating disease.